2015
DOI: 10.3390/biom5021079
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Haskap Cultivars is Polyphenols-Dependent

Abstract: Haskap (Lonicera caerulea L.) berries have long been used for their health promoting properties against chronic conditions. The current study investigated the effect of Canadian haskap berry extracts on pro-inflammatory cytokines using a human monocytic cell line THP-1 derived macrophages stimulated by lipopolysaccharide. Methanol extracts of haskap from different growing locations in Canada were prepared and characterized for their total phenolic profile using colorimetric assays and liquid chromatography—Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 43 publications
6
62
2
2
Order By: Relevance
“…Rich in polyphenols, honeysuckle berry shows a potential to scavenge free radicals and also demonstrated a potential to modify the TNF. A study by Rupasinghe et al [74] presented a negative correlation between polyphenol content of honeysuckle extracts and proinflammatory cytokines COX-2, TNF-α, interleukin-6 (IL-6) and prostaglandin (PGE 2 ). Inhibition of the inflammatory process was shown to be mostly effective at the start of the signaling cascade; thus, it can be assumed that honeysuckle berry extracts are more efficient in preventing the inflammation rather than treatment.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%
“…Rich in polyphenols, honeysuckle berry shows a potential to scavenge free radicals and also demonstrated a potential to modify the TNF. A study by Rupasinghe et al [74] presented a negative correlation between polyphenol content of honeysuckle extracts and proinflammatory cytokines COX-2, TNF-α, interleukin-6 (IL-6) and prostaglandin (PGE 2 ). Inhibition of the inflammatory process was shown to be mostly effective at the start of the signaling cascade; thus, it can be assumed that honeysuckle berry extracts are more efficient in preventing the inflammation rather than treatment.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%
“…The studies on bioactivity of haskap berries started only recently, therefore the results are still scarce. Some reports from both in vivo animal studies and in vitro cell line investigations showed that haskap berries may protect from inflammation and oxidation triggered diseases (Rupasinghe et al, 2015). Blue honeysuckle extract in rat model attenuated adjuvant-induced arthritis symptoms with crosstalk of anti-inflammatory and antioxidant effects (Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Murase et al (1999) and Calixto et al (2003) reported that plant constituents inhibited the arachidonic acid pathway, nitric oxide, ICAM-1, VCAM-1 and E-selectin in the vascular endothelial cells and suggested that this inhibition is due to the inhibition of IL-1B, TNF-a and NF-jB. Plant extract has the potential to act as an effective inflammation inhibitor (Rupasinghe et al 2015). Chlorogenic acid and rutin were polyphenols found in the highest concentrations in plant extract and have been implicated in inhibiting inflammatory transcription factors (Palikova et al 2009;Zdarilova et al 2010).…”
Section: Discussionmentioning
confidence: 99%